ANALISIS ETIKA DALAM PRODUKSI: PERAN PRODUSEN DALAM MENJAMIN KESEJAHTERAAN DAN KEPUASAN KONSUMEN PADA AR PERCETAKAN - Nur Muhammad Azka; Nurul Wulandari Putri (Cahaya Ilmu Bangsa, 2025)
In the context of the increasingly competitive printing industry, AR Printing is committed to implementing ethical principles that focus not only on financial gain, but also on the social and environmental impact of each product produced. Manufacturers at AR Printing ensure that the raw materials used are sourced from responsible and environmentally friendly suppliers, and implement transparent and fair production practices. In addition, attention to employee welfare is a major focus, where employees who feel valued and treated well tend to provide better service to consumers. This study explores the role of ethics in production at AR Printing, focusing on the responsibility of manufacturers in ensuring consumer welfare and satisfaction. Through a qualitative approach involving interviews and observations, this study identifies the ethical principles applied in the production process and their impact on consumer experience. The results show that the implementation of good business ethics not only improves the quality of products and services, but also builds consumer trust and loyalty. These findings confirm that a commitment to ethics in production is an important factor in creating a mutually beneficial relationship between producers and consumers, as well as contributing to the welfare of society as a whole.